Natural Larval Trematode Infections in Lymnea truncatula Populations in Elazig Province in Turkey - Kaplan, Mustafa; Kelestemur, Neslihan; Saglam, Naim; Gokhan, Haci Bayram; Baspinar, Serpil (Medwell Online, 2012)
Freshwater snails play a significant role as intermediate host in life cycles of trematodes. In addition to providing these parasites with a site for reproduction, freshwater snails are also carriers to reach them to their next hosts. It is obvious that infected snail carrying cercaria or metacercaria play an important role in the distribution of trematodes to their final hosts including farm animals and human beings. It was aimed to determine the larval trematode infection prevalence in Lymnea truncatula populations in Elazig. Total of 191 L. truncatula samples were collected from three regions in Icme town and two regions around Hazar lake in Sivrice town making a total of five regions. Shell lengths of L. truncatula were 0.6-15 (8.90 +/- 4.5) mm and shell widths showed a range of 0.3-0.8 (0.54 +/- 0.1) mm. Of the 14 (7.3%) of L. truncatula samples studied under stereomicroscope by applying pressure and carrying out dissection, trematode larvae were established. While a significant difference was not observed between shell lengths and the presence of trematode larvae, a significant difference was found between shell width and the presence of trematode larvae.
Keywords: Lymnea truncatula; larval infection; trematode; snail; Elazig; Turkey